Traumatic internal carotid artery dissection presenting as delayed hemilingual paresis. - Pica, R A; Rockwell, B H; Raji, M R; Dastur, K J; Berkey, K E (American Journal of Neuroradiology, 1996)
A case of internal carotid artery dissection presenting as delayed right hemilingual paresis after blunt craniocervical trauma is presented. Diagnosis is discussed with emphasis on MR and MR angiographic findings. Mechanisms of injury and lower cranial nerve palsy are also briefly discussed.